Transgender emergence in video games - Robin Longobardi Zingarelli (Eludamos)
Over the past two decades, trans theory has conceptualised gender identity and bodily autonomy, advocating for self-exploration and political affirmation (Nagoshi & Brzuzy, 2010; Stryker, 2017; Stryker & Whittle, 2006). This focus has resonated with game studies, which have examined video games as a medium for trans representation (Ruberg, 2020; Ruberg, 2022; Thach, 2021). This commentary explores the emergence of transgender identities in video games, outlining the state of the art of transgender representations and the experiences of trans players and designers. It highlights the significance of procedural elements such as character customisation, embodiment, and player-avatar relationship for transgender players. In doing so, it also suggests potential tensions and contradictions inherent in transgender emergence, arguing that while video games can provide positive and beneficial spaces for exploring gender identity, they may simultaneously perpetuate transphobia and exploit transgender experiences.